Well-Being in Germany: GDP and Unemployment Still Matter - Johannes Vatter (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2012)
This paper examines regional differences in subjective well-being (SWB) in Germany. Inferential statistics indicate a diminishing but still significant gap between East and West Germany, but also differing levels of SWB within both parts. The observed regional pattern of life satisfaction reflects macroeconomic fundamentals, where labor market conditions play a dominant role. Differing levels of GDP and economic growth have contributed rather indirectly to regional well-being such that the years since the German reunification can be considered as a period of joyless growth. Approximately half of the satisfaction gap between East and West Germany can be attributed to differing macroeconomic conditions. Moreover, we argue that it is advisable for governments to collect more data on aspects that presumably influence the well-being of society. For example, it is highly probable that reliable data on regional income inequality would lead to several important and influential studies. This, in turn, can help to design indicators for those characteristics which are known for affecting SWB. In total, we do not perceive any fundamental caveat for using data on SWB in order to measure welfare directly, at least within culturally and linguistically homogenous regions. To reduce statistical uncertainty, however, it would be helpful to include subjective information of this kind into larger cross-sectional surveys such as common census data.
Keywords: R10; I31; 330; social welfare; subjective well-being; unemployment; economic growth; Lebensqualität; Zufriedenheit; Arbeitslosigkeit; Sozialprodukt; Alte Bundesländer; Neue Bundesländer; Deutschland